2005
DOI: 10.1152/jn.00586.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Neurotransmission in the Cerebellar Interposed Nuclei: Involvement in Classically Conditioned Eyeblinks and Neuronal Activity

Abstract: The cerebellar interposed nuclei (IN) are critical components of a neural network that controls the expression of classically conditioned eyeblinks. The IN receive 2 major inputs: the massive, gamma-aminobutyric acid (GABA)-mediated input from the Purkinje cells of the cerebellar cortex and the relatively weaker, glutamate-mediated input from collaterals of mossy and climbing fiber cerebellar afferent systems. To elucidate the role of IN glutamate neurotransmission in conditioned response (CR) expression, effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Cortical lesions and pharmacological corticonuclear disconnections have been reported to "unmask" short-latency CRs (Perrett et al, 1993;Bao et al, 2002;Ohyama et al, 2006;Vogel et al, 2009). Discrete inactivations of periocular microzone regions in our study were able to abolish CRs, but no short-latency responses were observed, in agreement with Attwell et al (2002) and Aksenov et al (2005).…”
Section: Periocular Microzones In Lobule Hvi Are Critical For Expresssupporting
confidence: 80%
See 1 more Smart Citation
“…Cortical lesions and pharmacological corticonuclear disconnections have been reported to "unmask" short-latency CRs (Perrett et al, 1993;Bao et al, 2002;Ohyama et al, 2006;Vogel et al, 2009). Discrete inactivations of periocular microzone regions in our study were able to abolish CRs, but no short-latency responses were observed, in agreement with Attwell et al (2002) and Aksenov et al (2005).…”
Section: Periocular Microzones In Lobule Hvi Are Critical For Expresssupporting
confidence: 80%
“…Such small volumes are unlikely to have spread to the cerebellar nuclei. Moreover, nuclear blockade of glutamatergic transmission has little or no effect on CRs Aksenov et al, 2005). Cortical lesions and pharmacological corticonuclear disconnections have been reported to "unmask" short-latency CRs (Perrett et al, 1993;Bao et al, 2002;Ohyama et al, 2006;Vogel et al, 2009).…”
Section: Periocular Microzones In Lobule Hvi Are Critical For Expressmentioning
confidence: 99%
“…6). These observations are incompatible with notions that SLRs reflect nonassociative changes resulting from disinhibiting the AIN (Attwell et al, 2002), increases in tonic AIN activity levels (Aksenov et al, 2005), or cell-wide increases in the intrinsic excitability of AIN neurons (Aizenman and Linden, 2000;Zhang et al, 2004). Rather, they suggest that SLRs reflect an associative and input-specific form of AIN plasticity.…”
Section: Experiments 5: Slrs Are Learned and Associativementioning
confidence: 65%
“…3, top left, blue), as well as the failure of similar infusions to abolish the expression of normal conditioned responses (Attwell et al, 2002;Aksenov et al, 2005), appear to contradict the proposed hypothesis. However, glutamate blockade may be incomplete because of either low-drug concentrations or a wider area of inactivation required compared with muscimol.…”
Section: Functional Contributions Of Plasticity In the Ainmentioning
confidence: 95%
“…These investigators interpret the first type to facilitate the lid closing orbicularis oculi (OO) muscle and the latter to promote activation of the lid opening levator palpebrae muscle with reflex blinks. In the rabbit, most anterior IP neurons exhibit elevated activity followed by a pause in activity starting ϳ50 ms after an air puff unconditioned stimulus (Aksenov et al, 2004(Aksenov et al, , 2005. In recordings from the anterior IP of rats, an intense periorbital shock generates a burst of activity (Freeman and Nicholson, 2000).…”
Section: Introductionmentioning
confidence: 99%